Acúmulo de matéria seca e nutrientes e resposta do tomateiro caeté a doses de nitrogênio e fósforo - Diógenes, Talita Barbosa Abreu (Universidade Federal Rural do Semi-Árido, 2016)
With the use of new farming techniques, add high productive potential genetic material arises, the need to assess the nutritional requirements of tomato producing areas. Thus, in order to evaluate the accumulation of dry matter and nutrients by ‘Caeté’ tomato, and its response to nitrogen and phosphorus doses, two experiments were conducted. The first was conducted in Fazenda Terra Santa, municipality of Quixeré-CE, between the months of June and September 2013, in an area of commercial plantations, which were evaluated the accumulation dry matter and nutrients by sampling tomato plants to 14, 28, 42, 56, 70, 84 and 99 days after transplanting (DAT). The second experiment was conducted at Fazenda Boágua, municipality of Baraúna-RN, from August to October 2014. The experimental design was a randomized block with four replications. The treatments consisted of five nitrogen rates (0, 60, 120, 240 and 360 kg ha-1 of N) and five doses of phosphorus (0, 75, 150, 300 and 600 kg ha-1 P2O5). The total estimated production of dry matter was 912.84 g plant-1, with the largest accumulations of nutrients in the fruiting stage, the fruits being the preferred drains. The macro and micronutrients accumulation order by tomato plants at 99 DAT was respectively K> N> Ca> S> Mg> P and Fe> Mn> B> Zn> Cu. The nitrogen, phosphorus and potassium were accumulated in large quantities in fruits. For micronutrient accumulation was higher in the vegetative to the fruit. Nitrogen and phosphorus doses that provided the highest commercial yields were 45 and 311 kg ha-1, respectively. Nitrogen and phosphorus in the diagnostic sheet increased with the addition of N rates and P2O5 to the ground. Tomato 'Caeté' fertilized with 60 and 150 kg ha-1 of N and P2O5, accumulated 36.30 and 2.83 kg ha-1 of nitrogen and phosphorus in the fruits, respectively
Keywords: Solanum lycopersicum L; Crescimento; Extração de nutrientes; Nutrição mineral; Solo alcalino; Solanum lycopersicum L; Growth; Nutrient extraction; Mineral nutrition; Alkaline soil; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO